Review of monograph - Svechnikov, S.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
Review of monograph: A.A. Akopyan, O. Yu. Borkovskaya, N.L. Dmitruk, A.V. Karimov, R.V. Konakova, V.V. Melenin, A.V. Sachenko, M.N. Tursunov, D.M. Yodgorova. "Photoconverters with AlGaAs/GaAs Heterojunction on Textured GaAs Substrates (Physico-Technological aspects) -Fan Publishers, Tashkent, 2004